EFEK PENAMBAHAN EKSTRAK AIR JAHE (Zingiber officinale Roscoe) DAN PENYIMPANAN DINGIN TERHADAP MUTU SENSORI IKAN TUNA (Thunnus albacores) - Harikedua, Silvana Dinaintang (Sam Ratulangi University, 2010)
The objective of this study was to investigate the effect of ginger extract addition and refrigerate storage on sensory quality of Tuna through panelist’s perception. Panelists (n=30) evaluated samples for overall appearance and flavor attribute using hedonic scale 1–7. The sample which is more acceptable by panelists on flavor attributes having 3% gingers extract and storage for 3 days. The less acceptable sample on flavor attribute having 0% ginger extract and storage for 9 days. On the other hand, the sample which is more acceptable by panelists on overall appearance having 0% ginger extract without storage treatment. The less acceptable sample on overall appearance having 3% ginger extract and storage for 9 days.